PERAN SUAMI DAN ISTRI DI ERA MILENIAL DALAM PERSPEKTIF HUKUM KELUARGA ISLAM (Studi di Wilayah Kecamatan Lut Tawar ) - Rizka Selvia Tarmulo; Soraya Devy; Jamhuri (Prodi Magister Hukum Keluarga Pascasarjana UIN Ar-Raniry Banda Aceh, 2024)
The division of roles between husband and wife occurs because of the marriage bond. Sometimes the division of roles between husband and wife is considered unequal between one party, which can cause several conflicts. So, in order to create a harmonious family, the division of roles between husband and wife is made by mutual agreement. This research was conducted in Lut Tawar District, Central Aceh Regency. The purpose of this research is to see how the roles of husband and wife are divided in millennial families in the district. Lut Tawar and looked at the perspective of Islamic family law in the division of roles of husband and wife in millennial families in the district. Lut Tawar. The research method uses empirical research, with a qualitative approach. The results are described in the form of descriptive analytical data. The results of the research state that there are two forms of division of roles between husband and wife in millennial families in Kec society. Lut Tawar, including divisions that adopt a fully egalitarian approach and divisions that adopt an egalitarian approach but are still shackled by understanding the patriarchal cultural system. In the perspective of Islamic family law, the division of roles of husband and wife in millennial families in the community of Kec. Lut Tawar continues to follow the principles contained in religious provisions, only adapted to the context of changing times. In millennial families, there is greater emphasis on equality and balance in husband and wife relationships, as well as emphasizing the importance of mutual respect, cooperation and sharing responsibilities between husband and wife in accordance with Islamic principles of justice and love in the household.